A Study on uses of ICT in Integrate University Library: The Impact of ICT on Integrate University Libraries (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Libraries as we once knew them have evolved in response to the rapid advancements ininformation and communication technologies (ICTs). More robust and adaptable than their predecessors,today's Integrate libraries also have the ability to reach consumers across regional boundaries. Librariesare rapidly converting to digital format, making their collections available online and to a global audience.Libraries have adapted their services to accommodate a global audience and have emerged as vitalcommunity hubs as a result of advances in information and communication technologies. Because theyallow for more interoperability and information exchange, ICTs in libraries are increasingly popularamong patrons. Under one roof, users have access to a plethora of informational resources, includingtext, sound, photos, etc. As a result, libraries may better serve their communities and become integralcogs in the information society by adopting ICTs. Integrate libraries are allowing for better, moreimmediate information communication among academics and are breaking down geographical barriersto distance education. Aiding in the dissemination of knowledge, it reaches places that would otherwisebe inaccessible. The library industry has seen radical change recently, with the widespread adoption ofdigital library systems replacing traditional print libraries. Libraries have shifted their focus from print todigital collections as a result of the proliferation of information and communication technologies and thewidespread availability of high-speed networks on a national and international scale.